The Impact of Ice Compression and Massage Techniques on Lactate Removal and Interleukin-6 Concentrations During Halftime Recovery in Intermittent Sports - Rusdiawan, Afif; Widodo, Achmad; Lani, Ahmad; Özman, Cemal; Putra, Ardo Yulpiko; Susanto, Nugroho; Munandar, Rizky Aris; Kafrawi, Muhammad Firdaus; Irmawati, Farizha (Physical Education Theory and Methodology, 2025)
Background. High-intensity intermittent sports increase blood lactate levels and inflammatory markers such as interleukin-6 (IL-6), which may hinder recovery and performance. Effective recovery strategies are crucial for enhancing lactate clearance and regulating inflammation. Objectives. This study aimed to evaluate the effects of 15-minute ice compression and sport massage interventions during halftime on athletes’ lactate clearance and IL-6 levels. Materials and Methods. Thirty-six male soccer players, aged 18 to 24 years, were randomly assigned to one of three groups for this experimental study: ice compression (IC, n = 12), sport massage (SM, n = 12), and passive recovery (PR, n = 12). Each participant completed a standardized exercise regimen designed to induce fatigue. The PR group rested passively after the workout, while the intervention groups received a massage or ice compression for 15 minutes. Blood lactate and IL-6 levels were assessed before exercise (T0), immediately after (T1), and fifteen minutes post-exercise (T2). To analyse the differences observed, a mixed-model ANOVA and post-hoc tests (Bonferroni/Games-Howell) were performed. Results. According to the results obtained, the lactate levels (IC: ΔT1-T2 = -2.34 ± 0.96 mmol/L, d = 2.209; SM: ΔT1-T2 = -1.39 ± 0.79 mmol/L, d = 0.829) and IL-6 levels (IC: ΔT1-T2 = -1.44 ± 0.93 pg/mL, d = 1.206; SM: ΔT1-T2 = -1.58 ± 0.63 pg/mL, d = 1.645) were both significantly lower than PR (p < 0.05). Although IC and SM exhibited similar anti-inflammatory effects (p = 0.898), IC demonstrated superior lactate clearance compared to SM (p = 0.023, d = -1.081). PR showed only minimal decreases in both biomarkers. Conclusions. Massage and ice compression effectively enhance lactate clearance after high-intensity exercise, with massage offering additional benefits in reducing IL-6-mediated inflammation. These findings support massage as an excellent recovery method for athletes requiring immediate physiological repair following exertion.